2019
DOI: 10.4085/1062-6050-406-18
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography of Gluteal and Fibularis Muscles During Exercises in Individuals With a History of Lateral Ankle Sprain

Abstract: Context Individuals with a history of lateral ankle sprains (LASs) have ankle and hip neuromuscular changes compared with those who do not have a history of LAS. Objective To compare gluteus maximus (GMax), gluteus medius (GMed), and fibularis longus and brevis muscle activation using ultrasound imaging during tabletop exercises and lateral resistance-band walking in individuals with or without a history of LAS or chronic ank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 30 publications
(53 reference statements)
1
22
0
Order By: Relevance
“…These findings are similar to the increased activation ratio (AR) measured in the fibularis and gluteal muscle groups in the same participants. 31 In the unadjusted analysis, both Coper and CAI groups demonstrated moderate, significant decreases in nonresisted QP AR compared with controls. Furthermore, the CAI group demonstrated large, significantly decreased resisted ARs in the QP compared with both LAS and control groups.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…These findings are similar to the increased activation ratio (AR) measured in the fibularis and gluteal muscle groups in the same participants. 31 In the unadjusted analysis, both Coper and CAI groups demonstrated moderate, significant decreases in nonresisted QP AR compared with controls. Furthermore, the CAI group demonstrated large, significantly decreased resisted ARs in the QP compared with both LAS and control groups.…”
Section: Discussionmentioning
confidence: 89%
“…Another study employed USI to compare gluteal muscle thickness and activation during side-lying table top abduction and band-walking exercises in the same participants. 31 One of the primary observations was that the gluteus medius AR in CAI group was significantly smaller contrasted to Copers, LAS, and healthy controls as task difficulty increased. 31 In addition, neuromotor compensations were observed, as the CAI group relied more on the gluteus maximus muscle to complete the exercise.…”
Section: Discussionmentioning
confidence: 99%
“…27 One of the primary observations was that the gluteus medius AR in CAI group was significantly smaller contrasted to Copers, LAS, and healthy controls as task difficulty increased. 27 In addition, neuromotor compensations were observed, as the CAI group relied more on the gluteus maximus muscle to complete the exercise. 27 The authors suggested this may be due to central motor alterations that occur after injury that may affect the motor recruitment in the area.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are similar to the increased AR measured in the fibularis and gluteal muscle groups in the same participants. 27…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation